Second-line treatment of EGFR T790M-negative non-small cell lung cancer patients. (November 2019) - Liao, Bin-Chi; Griesing, Sebastian; Yang, James Chih-Hsin
Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are the currently recommended treatment for advanced EGFR mutation-positive non-small cell lung cancer (NSCLC). Acquired resistance inevitably develops, with the EGFR T790M mutation comprising approximately 55% of the mechanisms of resistance following first- or second-generation EGFR-TKI therapy (e.g. gefitinib, erlotinib, afatinib, and dacomitinib). Patients without T790M are a heterogeneous group for whom platinum-based chemotherapy is currently recommended as a second-line treatment. In addition to secondary mutations in EGFR (e.g. T790M), the currently known resistance mechanisms can be classified into the following three categories: bypass pathways, downstream signaling pathways, and histologic transformations. Given the evolving knowledge and convenience of diagnosing acquired resistance mechanisms by next-generation sequencing and liquid biopsy, exploratory studies targeting these resistance mechanisms and incorporating immunotherapy into the treatment paradigm have become the mainstream of future development. This review focuses on acquired resistance mechanisms other than T790M that develop after first- or second-generation EGFR-TKI therapy. Exploratory second-line treatments targeting resistance mechanisms as well as combination immunotherapy and chemotherapy in ongoing clinical trials are reviewed here. We also highlight the recent development of next-generation sequencing and liquid biopsy in this field.